Assessing the role of large herbivores in the structuring and functioning of freshwater and marine angiosperm ecosystems. Issue 2 (22nd September 2015) - Bakker, Elisabeth S.; Pagès, Jordi F.; Arthur, Rohan; Alcoverro, Teresa
Abstract : While large herbivores can have strong impacts on terrestrial ecosystems, much less is known of their role in aquatic systems. We reviewed the literature to determine: 1) which large herbivores (> 10 kg) have a (semi‐)aquatic lifestyle and are important consumers of submerged vascular plants, 2) their impact on submerged plant abundance and species composition, and 3) their ecosystem functions. We grouped herbivores according to diet, habitat selection and movement ecology: 1) Fully aquatic species, either resident or migratory (manatees, dugongs, turtles), 2) Semi‐aquatic species that live both in water and on land, either resident or migratory (swans), 3) Resident semi‐aquatic species that live in water and forage mainly on land (hippopotamuses, beavers, capybara), 4) Resident terrestrial species with relatively large home ranges that frequent aquatic habitats (cervids, water buffalo, lowland tapir). Fully aquatic species and swans have the strongest impact on submerged plant abundance and species composition. They may maintain grazing lawns. Because they sometimes target belowground parts, their activity can result in local collapse of plant beds. Semi‐aquatic species and turtles serve as important aquatic–terrestrial linkages, by transporting nutrients across ecosystem boundaries. Hippopotamuses and beavers are important geomorphological engineers, capable of altering the land and hydrology at landscape scales. Migratory species and terrestrial species with large home ranges are potentially important dispersal vectors of plant propagules and nutrients. Clearly, large aquatic herbivores have strong impacts on associated species and can be critical ecosystem engineers of aquatic systems, with the ability to modify direct and indirect functional pathways in ecosystems. While global populations of large aquatic herbivores are declining, some show remarkable local recoveries with dramatic consequences for the systems they inhabit. A better understanding of these functional roles will help set priorities for the effective management of large aquatic herbivores along with the plant habitats they rely on.